THE ROLE OF THE FAMILY IN THE SOCIO-CULTURAL DEVELOPMENT OF SOCIETY - Mirzakholov Khojiakbar (Scholar Express Journal, 2022)
This article discusses the role of the family in the socio-cultural development of society. The author gives a detailed description of the concept of family. The article analyzes the impact on the social, spiritual and cultural life of the family
Keywords: Family; Society; Social Development; Cultural Development